GAMBARAN FAKTOR PENYEBAB PROKRASTINASI AKADEMIK SISWA SMA KELAS XI SMAN 1 BATUJAJAR DIMASA PANDEMI COVID-19 - Irma Wulandari; Siti Fatimah; Maya Masyita Suherman (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2021)
The current condition of the pandemic Covid-19 has caused the government to implemented online learning. Students are required to be able adapted the new conditions, namely learning through online media that can help students learn during the pandemic Covid-19. The purposed of this study was to described the factors causing academic procrastination of class XI IPS 5 students at SMAN 1 Batujajar during the pandemic Covid-19. This research used descriptive qualitative method.  The data collection techniques used such as interviews, observation and documentation. Based on the results of the research, the factors that cause academic procrastination to the four students, students do not understand the material presented by the teacher, students are not confident in their abilities, students are not able to manage time to do assignments with other activities, students feel bored because of online learning at home, lack of attention and encouragement of motivation to learn from parents, and constraints on signals, handphone, internet quotas.Keywords: Pandemic Covid-19, Academic Procrastination